The role of agricultural R&D within the agricultural innovation systems framework - Anandajayasekeram, Ponniah (International Food Policy Research Institute, 2011)
This paper traces the evolution of the innovation systems framework within the agricultural sector in Sub-Saharan Africa, and presents a conceptual framework for agricultural innovation systems. The difference between innovation ecology/ecosystems and intervention-based innovations systems is highlighted, given that these two concepts are used at different levels in promoting and sustaining agricultural innovations. The role of open innovation, innovation platforms, and innovation intermediaries in catalyzing, enhancing, and facilitating the innovation process are discussed, as is the role of R&D in the innovation process. The paper goes on to consider the interconnectedness of the innovation systems perspective and value-chain analysis in agricultural R&D processes, before summarizing the current status of agricultural R&D in Sub-Saharan Africa, lessons from past experience, and implications and key challenges confronting development practitioners in institutionalizing the agricultural innovation systems concept within the agricultural R&D in the region. Finally, some key conclusions and areas for investment are presented.